Upaya Mempertahankan Bisnis Radio Siaran Di Era Kemajuan Teknologi Informasi (Studi Pada Empat Perusahaan Radio Siaran di Kabupaten Kebumen) - Hendrawan Prasetyo (P4M STIE Putra Bangsa, 2019)
The problem in this study is about how the radio broadcast business in the era of technological advancements and information, whether radio broadcasts can still maintain their existence and are still in the public interest as an effective means of entertainment and information and what radio broadcast companies do in facing business challenges in the era technological progress and information so that it can survive. The method used in this study is a qualitative research method, taking data sources using a